A re-reading of Gandhi's and Ambedkar's emancipatory discourses for social action against untouchability. (17th December 2021) - Biswas, Sujay
Abstract: Gandhi and Ambedkar offer a fascinating picture of community organizers fighting against caste oppression and caste discrimination. Both were committed to transforming the social, economic, political, and cultural conditions of 'Dalits' † . They claimed that only through social action could societal transformation take place. As a result, they placed a strong emphasis on mobilizing the public against untouchability. They envisioned the removal of untouchability through popular struggles and popular participation. Not only did Gandhi and Ambedkar undertake popular campaigns, but they also saw them as necessary and beneficial. This paper explores the implications of integrating the constructs of the Gandhian and Ambedkarian models to tackle the problem of untouchability. It re-reads the Constitution of the Anti-Untouchability League (AUL) which was prepared by Gandhi himself in January 1935 in conjunction with a comprehensive letter penned by Ambedkar in November 1932, containing a plan of action for the AUL to carry out for the uplift of 'Dalits', to shed light on the lessons that are still important for the modern-day community organizers in India. The paper argues that synergizing Gandhi's and Ambedkar's emancipatory discourses can enrich the present-day activism for social action combatting untouchability.